1987
DOI: 10.1007/bf00385055
|View full text |Cite
|
Sign up to set email alerts
|

Foraging time allocation in relation to sex by the gulf coast fiddler crab (Uca panacea)

Abstract: Schoener (1971) proposed that the reproductive demands of animals should be important in shaping their foraging behavior because fitness is affected. He defined two forager types: energy maximizers (reproductive success depends on energetic intake) and time minimizers (reproductive success depends on time spent in activities other than foraging), and suggested that females most often illustrate the former and males the latter. We tested whether mating activities influence the foraging behavior of Uca panacea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…Most species are diurnal and work to a tight schedule of a few hours a day with most of their time spent feeding, while the remaining time is divided between burrow maintenance, social interactions, grooming and predator avoidance (e.g. Caravello and Cameron, 1987;Crane, 1975;Wolfrath, 1993). Each crab operates from its own burrow, which it defends vigorously against other crabs.…”
mentioning
confidence: 99%
“…Most species are diurnal and work to a tight schedule of a few hours a day with most of their time spent feeding, while the remaining time is divided between burrow maintenance, social interactions, grooming and predator avoidance (e.g. Caravello and Cameron, 1987;Crane, 1975;Wolfrath, 1993). Each crab operates from its own burrow, which it defends vigorously against other crabs.…”
mentioning
confidence: 99%
“…The sex ratio biased in favor of males is a widely accepted trend for adult fiddler crabs, since male dominance has been recorded for many species collected by different sampling procedures ( Johnson, 2003). The causes of this sex ratio pattern are historically related to differential growth rates, migration, spatial and temporal variation in the use of resources, and differential behavior patterns related to sex (Montague, 1980;Salmon, 1987;Caravello and Cameron, 1987;Spivak et al, 1991;Macia et al, 2001;Costa and Negreiros-Fransozo, 2003;Hayes et al, 2013). However, Johnson (2003) concluded that high female mortality rate, probably due their high energy investment in reproduction, is the principal cause of the notable sex ratio bias toward males in fiddler crabs populations.…”
Section: Sampling Technique For Fiddler Crab Populationsmentioning
confidence: 99%
“…Females possess two minor claws. It is well documented that during feeding the animal uses only the minor claw, which places males at a considerable disadvantage and results in a number of sexually dimorphic aspects of feeding (Valiela et al 1974;Crane 1975;Caravello and Cameron 1987;Weissburg 1993). The most fundamental difference among males and females is the existence of sexually dimorphic feeding energetics that produce sex-specific rules governing the departure of foragers from feeding patches (Weissburg 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Males are unable to sustain positive energy balances at low food levels, and they cease foraging in patches in which females continue to feed. Males exhibit stronger preferences for more food rich patches in behavioral choice experiments (Weissburg 1990), and in the field preferentially exploit zones of high food abundance (Murai et al 1983;Caravello and Cameron 1987). Females more commonly exploit low density patches in laboratory patch choice experiments (Weissburg 1990), and in the field aggregate in poorer quality areas near burrows (Murai et al 1983;Caravello and Cameron 1987).…”
Section: Introductionmentioning
confidence: 98%